On a class of nonlinear reaction-diffusion systems with nonlocal boundary conditions - Abdelfatah Bouziani (Abstract and Applied Analysis)
We prove the existence, uniqueness, and continuous dependence of a generalized solution of a nonlinear reaction-diffusion system with only integral terms in the boundaries. We first solve a particular case of the problem by using the energy-integral method. Next, via an iteration procedure, we derive the obtained results to study the solvability of the stated problem.